Through the Lens of One Day Last December: A Poetics of Narrative Teaching (LEARNing Landscapes, 2010)
Thoughtful teaching requires the mapping of one’s own life, a land marked with features of recalled sites. In the studio of my own classroom practice, working material resides in the poetic groundwork of after-school treks along contours of a New England shoreline. A black stone library. A harbor sound. The placement of a dogwood by a marshy pond. Through the lens of one day last December, read on…
Keywords: teaching; classroom practice; poetry